Detection, Evaluation and Mitigation of Resource Afﬁnity and Communication Contention Problems in a Task-Based Runtime over Heterogeneous Clusters - Nesi, Lucas Leandro; Schnorr, Lucas (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2020)
The complexity of high performance computing (HPC) platforms The Task-Based presents challenges in parallel application development. paradigm is a candidate to reduce some of the programmer's burden. However, because of the platforms' complexity, resource afﬁnity and communication contention might cause performance problems. This work presents a case study of these problems employing the Chameleon dense algebra linear solver LU factorization using the Task-Based runtime StarPU over 21 heterogeneous nodes. We present possible conﬁgurations to mitigate performance degradation and conduct an extensive analysis of their interaction. The results show a performance improvement of 16% without changing the application source code.